Espondilitis anquilopoyética: una reflexión y una interrogante - Annia Deysi Hernández Martín; Ibars Puerto Noda; Arelys Falcón Hernández (Universidad de las Ciencias Médicas de Cienfuegos, 2014)
Ankylosing spondylitis is a chronic inflammatory disease that affects the synovial membrane, joint entheses and para-articular structures of the spine, including the sacroiliac joints and limbs. We present a case of ankylosing spondylitis that had evolved for 12 years despite the relatively early diagnosis and treatment, showing flexion deformity and limitation of spinal movements. On radiological examination an early evolution to ankylosis was observed, which motivated us to make a reflection and a question.